IMPLEMENTASI STRATEGI PAIKEM DALAM MENINGKATKAN MOTIVASI BELAJAR SISYA DI PASRAMAN SAMIAGA - Sintia, Ni Kadek (Bawi Ayah: Jurnal Pendidikan Agama dan Budaya Hindu, 2024)
Abstract This article aims to analyze the implementation of Active, Innovative, Creative, Effective, and Fun Learning (PAIKEM) strategies in increasing the motivation of students in Pasraman Samiaga. Pasraman is a Hindu educational institution that has a crucial role in realizing a moral and intellectual young generation. However, monotonous learning, multi-grade learning system, lack of use of technology, and the gap between the material needed and received are some of the things that affect sisya's learning motivation. As one of the acarya's efforts in Pasraman Samiaga is to implement the PAIKEM strategy. This research uses a qualitative approach with data collection methods through non-participant direct observation, direct unstructured interviews, and documentation studies. Data analysis in this study was carried out through data reduction, data presentation, and conclusion drawing. The results of data analysis show that the implementation of Active, Innovative, Creative, Effective, and Fun Learning (PAIKEM) strategies in Pasraman Samiaga can increase student learning motivation. This can be seen from the increase in enthusiasm for learning, students do not feel pressured or tense, students are encouraged to be active and not bored, students are motivated to study harder, students ask teachers or friends when there is material that they do not understand, realize the importance of learning, and believe that the efforts made will not be lost. Keywords: Strategy, PAIKEM, Learning Motivation, Pasraman